Pengaruh Struktur modal, Likuiditas, dan Profitabilitas Terhadap Nilai Perusahaan Sektor F&B yang Terdaftar di BEI - alffiya, Alfiya; Yantiana, Nella (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
This study focuses on the value of companies in the food and beverage sector listed on the Indonesia Stock Exchange (IDX) during the 2019-2023 period. This study aims to examine the effect of capital structure, liquidity, and profitability on company value. Capital structure is measured using the debt to equity ratio (DER), liquidity is measured using the current ratio (CR), and profitability is measured using ROA and company value as a dependent variable is measured using price to book value (PBV). The sample used includes 26 companies that are routinely registered on the IDX for 5 years, with data obtained from the company's official website and the IDX. The analysis method used is multiple linear regression assisted by SPSS software. This study is quantitative with a secondary data approach and purposive sampling technique. The findings of the analysis indicate that capital structure variable represented by debt to equity ratio (DER) has a positive and significant effect on firm value, as measured by the Price to Book Value (PBV) indicator. For the DER variable, the t-count = 2.075 was obtained through its significance (p) = 0.040. T-table (two-sided, α = 0.05, df = 118) is around 1.980. Because t-count (2.075) exceeds t-table (1.980) and p = 0.040 < 0.05. From these results it can be interpreted that DER is proven to have a significant effect on firm value.